The Liquid Phase Deposition of ZnPtBNs: Study on Structural, Morphology, and Their Sheet-Resistant - Umar, Marjoni Imamora Ali; Mardiani, Mardiani; Mawarnis, Elvy Rahmi; Umar, Akrajas Ali (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
This paper reports ZnPt bimetallic nanoparticles (ZnPtBNs) synthesis through the liquid phase deposition (LPD) of of Zn(NO3)2.6H2O onto the indium-titanium oxide (ITO) substrates at various concentrations. The Effects of growth solution, the morphology, structural, and sheet resistance were studied. After preparation, the materials were characterized by using field emission electron microscopy (FESEM), energy dispersive X-ray (EDX), X-ray diffraction (XRD) and Four Point Probe (FPP) measurement by using Keithley 2401 source-meter. By inserting a growth solution into the ITO substrate the ZnPtBNs was successfully in-situ prepared. The synthesized ZnPtBNs exhibited homogeneous, fibrous at the (111) orientation with an average diameter of 100-700 nm. The atomic ratio of Zn:Pt and sheet resistance of ZnPtBNs decreased with the increase of Zn(NO3)2.6H2O concentration. The optimal elemental composition of the sample was at a ratio of Zn:Pt (1:25) obtained at 0.467 mM of Zn(NO3)2.6H2O. It showed the smallest sheet resistance (13.41 ?) which was 38% lower than the ITO sheet resistance (18.44 ?).